Learning from Damaged Historic Constructions: Recent Earthquakes in Turkey - Kishalı, Emre; Balcı, Esra; Almaç, Umut; Semiz, Nisa; Türer, Ahmet; Kambek, Erkan; Koç, Süheyla (Springer Science and Business Media B.V., 2026)
In February 2023, the southeastern region of Turkiye was struck by significant earthquakes along the Eastern Anatolian Fault Zone, resulting in widespread destruction and substantial loss of life. The intense ground movements caused severe damage to the area's architectural heritage, impacting numerous historic buildings that represent a range of periods, functions, scales, construction techniques, and materials. The regions affected by these earthquakes presented a unique opportunity for analysing the damage to cultural assets, a chance that may not present itself again for some time. It is crucial to collect data on the damage sustained by these structures and to leverage this knowledge for their future preservation. The quality of masonry walls in damaged buildings raises important concerns, particularly regarding the bond patterns and the quality of the binding mortar. Damage has also been observed in vaulted monuments. Many of these structures lack tie systems capable of withstanding lateral forces, which would enhance the structural behaviour during earthquakes. Additionally, past restoration efforts warrant attention, particularly in repair interventions such as reintegration; it has been noted that traditional construction practices were often overlooked. The structural relationship between old and new materials was not fully established, and insufficient measures were taken to reinforce this connection, rendering the repairs less effective. The text highlights the evaluation of earthquake damage at the scale of individual structures, with a particular emphasis on damage types associated with restoration practices implemented in the past. This methodology enables the development of appropriate recommendations to address conservation issues. The data used in this study were derived from various projects, particularly those focused on assessing architectural heritage affected by the February 2023 earthquakes, in which the authors were actively engaged.
Keywords: Assessment; Damage; Turkiye; Earthquake; Architectural Heritage; Restoration; Structure